2021
DOI: 10.48550/arxiv.2107.07244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multipolar nematic state of nonmagnetic FeSe based on the DFT+$U$

Takemi Yamada,
Takami Tohyama

Abstract: Clarifying the origin of nematic state in FeSe is one of urgent problems in the field of iron-based superconductivity. Motivated by the discovery of a nematic solution in the density-functional theory implemented by on-site Coulomb interaction (DFT+U ) [X. Long et al., npj Quantum Mater. 5, 50 (2020)], we reexamine the U dependence of electronic states in the nonmagnetic normal state of FeSe and perform full multipolar analyses for the nematic state. We find that with increasing U the normal state experiences… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…1 Under such the Lifshitz transitioned normal states for U > U LT , we have found that further increase of U stabilizes the symmetry broken nematic states above U =3.4 eV, as already shown in our previous study [11], where a multipolar nematic state becomes ground state with the hexadecapoles (Q 4α,x , Q 4α,y , Q 4β,x , Q 4β,y ) and multipoles (O xy , Q 4β,z ) corresponding to the E and B 2 irreducible representation of the D 2d point group at each Fe site (see table in Ref. [11]).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…1 Under such the Lifshitz transitioned normal states for U > U LT , we have found that further increase of U stabilizes the symmetry broken nematic states above U =3.4 eV, as already shown in our previous study [11], where a multipolar nematic state becomes ground state with the hexadecapoles (Q 4α,x , Q 4α,y , Q 4β,x , Q 4β,y ) and multipoles (O xy , Q 4β,z ) corresponding to the E and B 2 irreducible representation of the D 2d point group at each Fe site (see table in Ref. [11]).…”
Section: Resultssupporting
confidence: 87%
“…When U =0 eV, we have obtained ε kn > 0 at Γ and Z points as shown in Figs. 1 (a) and (b), yielding the three h-FSs consisting of the 28th, 29th, and 30th bands as shown in our previous study [11] and the DFT calculation of FeSe [7].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations